Stacking growth of ionically conductive MOF on biofabrics enables reliable NH3 sensor for hepatic encephalopathy diagnosis - Kai Liu; Yifan Xu; Xiaozhu Tian; Junxuan Liang; Zhihui Zhao; Jun Wang; Ziqi Zhang; Kewei Zhang; Song Yang (npj Flexible Electronics)
Abstract Aiming at the poor selectivity of electrically conductive metal-organic framework (EC-MOF) chemoresistive materials, this study develops a breakthrough room temperature ammonia (NH3) sensor by stacking ionically conductive MOF (IC-MOF) on an environmentally friendly biofabric. The synergism between ionic conductivity, tailored metal-nitrogen interaction, and fabric porosity enables the sensor with high response (R 0 /R g  = 14.7 towards 1 ppm NH3), low detection limit (36 ppb), and remarkable selectivity (coefficient >5.12 against common organic interferents). Notably, the optimized sensor yields a sixfold enhancement in response as compared with traditional EC-MOF powders. A linear regression model validated by fivefold cross-validation achieves 98.4% accuracy in NH3 concentration prediction, while the kNN classifier shows 96% accuracy in gas identification (tested on 192 samples). Preliminary clinical tests show that the sensor can clearly differentiate the exhaled NH3 signals of four patients with HE from those of healthy individuals, demonstrating the potential for non-invasive diagnostics.